Factors influencing the miss rate of polyps in a back-to-back colonoscopy study - Leufkens, A. M.; van Oijen, M. G. H.; Vleggaar, F. P.; Siersema, P. D. (Endoscopy, 2012)
Background and study aims: In patients undergoing colonoscopy, 22 % – 28 % of polyps and 20 % – 24 % of adenomas are missed. It is unclear which factors contribute to polyp miss rates, but colorectal cancer detected within 3 years after colonoscopy may originate from missed lesions. The aim of the current study was to determine patient- and polyp-related factors that influence the miss rates of polyps and adenomas during colonoscopy. Patients and methods: Data from 406 patients were obtained from a multicenter, randomized back-to-back colonoscopy study investigating the Third Eye Retroscope (TER) in improving polyp detection rate by visualizing hidden areas such as folds and curves. Patients were randomized to undergo standard colonoscopy followed by colonoscopy with TER, or vice versa. Miss rates were calculated for all polyps and adenomas. All lesions were categorized for size and location within the colon/rectum. Odds ratios (ORs) were computed using adjusted logistic regression models to identify factors independently associated with missed lesions. Results: The miss rate was 25 % (150 /611) for all polyps and 26 % (90 /350) for adenomas. Miss rates were significantly lower (21 % vs. 29 %) in patients randomized to TER as the first procedure (P < 0.03). Taking all groups together, > 2 polyps compared with ≤ 2 polyps detected during the first colonoscopy increased the risk of missing additional polyps (adjusted OR = 2.83; 95 % confidence interval [CI] 1.22 – 6.70). Adenomas in the left colon compared with adenomas in the right colon were also more frequently missed (adjusted OR = 1.65; 95 %CI 1.06 – 2.58). Conclusions: A quarter of polyps were missed during colonoscopy. Physicians should be aware that the risk of missing a polyp is related to patient factors (presence of > 2 polyps) and polyp factors (left colon location).